Fluid and combustion dynamics in dual-mode scramjets - Lee, Gyu Sub; Lee, Tonghun (Frontiers in Aerospace Engineering, 2023)
Burgeoning technological advancements in practical and efficient hypersonic flight is intertwined with the research and development of airbreathing hypersonic propulsion, specifically dual-mode scramjet (DMS) engines. Due fundamentally to the lack of complete understanding and adequate modeling of the fluid dynamics and combustion processes present in DMS’s, a large volume of academic works has been established towards characterizing the physical phenomena present in these engines. Significant differences in flame topologies, fluid interactions, and pressure profiles between scram and ram combustion are observed across these experimental and computational works. A focus on the dynamics responsible for combustion mode transition, choking and the propagation of the pseudoshock, is made, as is a discussion on the theoretical underpinning of the mechanisms behind flow choking and important choking thresholds. Further insight into the fundamental mechanisms and fluid and combustion physics present in DMS’s may improve future designs and operability of dual-mode scramjet engines.